Negative electrode material, secondary battery and electric equipment
By filling the silicon-based material and carbon material in the first amorphous carbon, the problems of poor expansion and compressive resistance of the silicon negative electrode material are solved, the energy density and cycling performance of the battery are improved, and the battery life is extended.
Patent Information
- Application Number
- CN202411596781.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-01-10
AI Technical Summary
The silicon negative electrode material is prone to expand during charging and discharging, resulting in deterioration of battery performance and shortening of cycle life, and poor compression and wetting performance.
The first amorphous carbon is used as a carrier to fill the silicon-based material and the carbon material with a filling degree of 30% to 80% to improve the compressive strength and compaction density, while leaving appropriate pores to ensure the wettability of the electrolyte and Ion mobility rate.
It improves the energy density and circulation performance of the battery, reduces the expansion of the negative electrode material, enhances the compressive resistance of the battery and the wetting ability of the electrolyte, and extends the service life of the battery.
Smart Images

Figure BDA0005127213260000141 
Figure BDA0005127213260000151 
Figure BDA0005127213260000181
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of secondary batteries, and specifically relates to a negative electrode material, a secondary battery and an electrical device. Background Art
[0002] With the development of science and technology and the increasing demand for mobile devices, the demand for mobile energy has skyrocketed. As a secondary battery, lithium-ion batteries have a long cycle life, no memory effect, and are environmentally friendly. They have been rapidly developed and widely used in the fields of consumer electronics and electric vehicles. However, driving range and battery safety have become two important factors affecting people's use of lithium-ion batteries.
[0003] In terms of driving range, it is mainly the energy density of the battery that determines the driving range of electric vehicles. The theoretical gram capacity of silicon is 4200mAh / g, so it has become a highly anticipated next-generation negative electrode material. The development of silicon negative electrodes is becoming more and more extensive. However, although the gram capacity of silicon negative electrodes is relatively high, they have more obvious disadvantages, mainly: a huge volume difference during charging and discharging. The volume of silicon increases by about 300% after charging than before charging. The volume expansion leads to the rupture and unlimited consumption of the SEI film, reducing the initial efficiency of the battery and causing the battery to produce gas. At the same time, the volume expansion will cause the silicon material to become powdered, and the pole piece will peel off and the pole piece will crack, causing serious damage to the pole piece structure, affecting the battery cycle life. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present application is to overcome the defects of the prior art such as the deterioration of battery performance caused by the easy expansion of silicon negative electrode materials, as well as the poor compression resistance and wetting properties of the negative electrode materials, thereby providing a negative electrode material, a secondary battery and an electrical device.
[0005] To this end, this application provides the following technical solutions:
[0006] According to one aspect of the present application, a negative electrode material is provided, comprising:
[0007] First, amorphous carbon has a plurality of pores;
[0008] an active material, the active material comprising a silicon-based material and a carbon material, at least a portion of the silicon-based material and at least a portion of the carbon material being distributed in the pores;
[0009] The filling degree of the silicon-based material and the carbon material in the first amorphous carbon is 30% to 80%, and the filling degree represents the ratio of effective pores of the first amorphous carbon filled by the silicon-based material and the carbon material.
[0010] In some optional embodiments, the negative electrode material satisfies at least one of the following conditions:
[0011] a. The specific surface area of the first amorphous carbon is 300 to 600 m 2 / g;
[0012] b. The total pore volume of the first amorphous carbon is 0.8 to 3 cm 3 / g;
[0013] c. In the first amorphous carbon, the mesopore volume accounts for 55% to 70% of the total pore volume of the first amorphous carbon.
[0014] In some optional embodiments, the carbon material includes a second amorphous carbon and a first graphitized carbon, and the second amorphous carbon includes at least one of conductive carbon black and coke;
[0015] And / or, the first amorphous carbon includes hard carbon.
[0016] In some optional embodiments, the second amorphous carbon includes secondary particles formed by aggregation of primary particles, the particle size of the primary particles of the second amorphous carbon is 20 nm to 100 nm, and the particle size of the secondary particles is 50 nm to 200 nm.
[0017] In some optional embodiments, the negative electrode material further includes a coating layer distributed on at least a portion of the surface of the first amorphous carbon, and the coating layer includes second graphitized carbon.
[0018] In some optional embodiments, the coating layer has a thickness of 0.5 μm to 5 μm.
[0019] In some optional embodiments, the compressive strength of the first amorphous carbon is 80 MPa to 200 MPa, and the compressive strength of the negative electrode material is 100 MPa to 250 MPa.
[0020] In some optional embodiments, the negative electrode material satisfies at least one of the following conditions:
[0021] 1) The specific surface area of the negative electrode material is 0.5 to 50 m 2 / g;
[0022] 2) The average particle size of the negative electrode material is 1 μm to 20 μm;
[0023] 3) Based on the total pore volume of the negative electrode material, the micropore volume of the negative electrode material accounts for 40% to 85%.
[0024] In some optional embodiments, the graphitization degree Id / Ig of the negative electrode material is 0.2 to 2.5.
[0025] In some optional embodiments, based on the total mass of the negative electrode material, the silicon-based material accounts for 5% to 30%.
[0026] According to another aspect of the present application, a secondary battery is provided, the secondary battery comprising a negative electrode plate, the negative electrode plate comprising the negative electrode material described above;
[0027] The peeling force of the negative electrode sheet is 20N / m to 30N / m.
[0028] According to another aspect of the present application, there is provided an electric device, comprising the above-mentioned secondary battery, wherein the secondary battery serves as a power supply for the electric device.
[0029] The technical solution of this application has the following advantages:
[0030] The negative electrode material provided by the present application includes: a first amorphous carbon having a plurality of pores; an active material at least partially distributed in the pores, the active material comprising a silicon-based material and a carbon material; the filling degree of the active material in the first amorphous carbon is 30% to 80%, and the filling degree indicates the proportion of the effective pores of the first amorphous carbon filled by the active material. By limiting the filling degree to the above range, the present application can improve the compressive strength and compaction density of the negative electrode material on the one hand, alleviate the expansion of the negative electrode material, and on the other hand, leave appropriate pores to ensure the wettability of the electrolyte, improve the ion migration rate, and achieve a positive effect on the battery performance. DETAILED DESCRIPTION
[0031] The following examples are provided for a better understanding of the present application, but are not limited to the best implementation mode described, and do not limit the content and protection scope of the present application. Any product identical or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the protection scope of the present application.
[0032] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0033] As analyzed in the background technology, the prior art uses hard carbon to coat silicon-based materials or fills silicon-based materials into porous hard carbon materials, but the electrolyte wettability and electrical properties need to be further improved. In order to solve these problems, the present application provides a negative electrode material, a secondary battery and an electrical device.
[0034] According to one aspect of the present application, a negative electrode material is provided, comprising:
[0035] First, amorphous carbon has a plurality of pores;
[0036] an active material, the active material comprising a silicon-based material and a carbon material, at least a portion of the silicon-based material and at least a portion of the carbon material being distributed in the pores;
[0037] The filling degree of the silicon-based material and the carbon material in the first amorphous carbon is 30% to 80%, and the filling degree represents the ratio of effective pores of the first amorphous carbon filled by the silicon-based material and the carbon material.
[0038] In some optional embodiments, the filling degree of the silicon-based material and the carbon material in the first amorphous carbon is 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, or within the range of any of the above values.
[0039] The present application deposits silicon-based materials and carbon materials inside the pores of the first amorphous carbon, and by limiting the filling degree within the above-mentioned range, on the one hand, it is possible to improve the compressive strength and compaction density of the negative electrode material and alleviate the expansion of the negative electrode material; on the other hand, it is possible to leave appropriate pores to ensure the wettability of the electrolyte, increase the ion migration rate, and achieve a positive effect on the battery performance, that is, to increase the energy density of the battery, and improve the cycle performance and rate performance of the battery.
[0040] In the present application, filling degree = 100% x volume of active material / effective pores of the first amorphous carbon. The effective pores refer to the pores in the first amorphous carbon that are connected to the outside, that is, open pores.
[0041] In the present application, a specific surface area meter is used to test the filling degree. The testing process is: testing the effective pore volume of the first amorphous carbon, recorded as A, testing the effective pore volume of the negative electrode material, recorded as B, and the filling degree is (AB) / A×100%.
[0042] In some optional embodiments, the negative electrode material satisfies at least one of the following conditions:
[0043] a. The specific surface area of the first amorphous carbon is 300 to 600 m 2 / g; As an example, the specific surface area of the first amorphous carbon is 300m 2 / g,350m 2 / g,400m 2 / g,450m 2 / g,500m 2 / g,550m 2 / g,600m 2 / g, or any of the above values within the range.
[0044] b. The total pore volume of the first amorphous carbon is 0.8 to 3 cm 3 / g; As an example, the total pore volume of the first amorphous carbon is 0.8cm 3 / g, 1.0cm 3 / g,1.2cm 3 / g,1.5cm 3 / g,1.7cm 3 / g, 2.0cm 3 / g,2.3cm 3 / g,2.5cm 3 / g,2.8cm 3 / g,3cm 3 / g, or any of the above values within the range.
[0045] c. In the first amorphous carbon, the mesopore volume accounts for 55% to 70% of the total pore volume of the first amorphous carbon; as an example, the mesopore volume accounts for 55%, 60%, 63%, 65%, 68%, 70% of the total pore volume of the first amorphous carbon, or is within a range composed of any of the above values.
[0046] In the present application, by limiting the specific surface area within the above range, the side reactions of the battery with the electrolyte during the lithium ion migration process are reduced; by limiting the total pore volume, the collapse of the structure can be avoided; by limiting the proportion of mesopore volume, it is shown that the first amorphous carbon has relatively more mesopores, which is more conducive to the subsequent introduction of active materials and reduces the processing difficulty; by limiting the three at the same time, the specific surface area can be reduced under the premise of introducing the same amount of active materials, thereby reducing the side reactions of the battery during the lithium ion migration process. The mesopore ratio is within the above range, which is conducive to ensuring the structural strength of the first amorphous carbon and inhibiting the expansion and contraction of the silicon negative electrode material during the charge and discharge process.
[0047] It should be noted that according to the definition of the International Union of Pure and Applied Chemistry (IUPAC), pores with a diameter less than 2 nm are called micropores; pores with a diameter greater than 50 nm are called macropores; pores with a diameter of 2 to 50 nm are called mesopores (or mesopores). In this application, the mesopore volume refers to the volume of pores with a pore diameter of 2 to 50 nm. In this application, the specific surface area, total pore volume and mesopore volume of the first amorphous carbon can be tested by methods and equipment known in the art. As an example, a specific surface area tester is used to test according to Part 4 of DB13 / T 2768.4-2018 Graphene Powder Material Detection Method.
[0048] In some optional embodiments, the carbon material includes a second amorphous carbon and a first graphitized carbon, and the second amorphous carbon includes at least one of conductive carbon black and coke;
[0049] And / or, the first amorphous carbon includes hard carbon.
[0050] In the present application, the first amorphous carbon is mainly used as an active material carrier, and the hard carbon is selected mainly for its porous and high strength properties; the second amorphous carbon is used to enhance the conductivity of the active material and buffer the expansion of the silicon-based material.
[0051] In some optional embodiments, the second amorphous carbon includes secondary particles formed by aggregation of primary particles, the particle size of the primary particles of the second amorphous carbon is 20nm to 100nm, and the particle size of the secondary particles is 50nm to 200nm. As an example, the particle size of the primary particles of the second amorphous carbon is 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, or within the range of any of the above values; the particle size of the secondary particles is 50nm, 80nm, 100nm, 120nm, 150nm, 180nm, 200nm, or within the range of any of the above values. In the present application, the second amorphous carbon inevitably agglomerates to form secondary particles during its growth process. When the primary particles and secondary particles of the negative electrode material are in the above range, it is beneficial to improve the conductivity of the negative electrode material.
[0052] In some optional embodiments, the negative electrode material further includes a coating layer distributed on at least a portion of the surface of the first amorphous carbon, and the coating layer includes second graphitized carbon.
[0053] In the present application, the coating layer is coated on the surface of the first amorphous carbon, which can reduce the side reaction between the negative electrode material and the electrolyte, and can limit the expansion degree of the internal silicon-based material, thereby inhibiting the expansion of the negative electrode material.
[0054] In some optional embodiments, the coating layer has a thickness of 0.5 μm to 5 μm. As an example, the coating layer has a thickness of 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, or within a range of any of the above values. By limiting the thickness of the coating layer, the present application can reduce the occurrence of side reactions and inhibit the expansion of the negative electrode material.
[0055] In some optional embodiments, the compressive strength of the first amorphous carbon is 80MPa to 200MPa, and the compressive strength of the negative electrode material is 100MPa to 250MPa. As an example, the compressive strength of the first amorphous carbon is 80MPa, 100MPa, 120MPa, 150MPa, 180MPa, 200MPa, or within the range formed by any of the above values; the compressive strength of the negative electrode material is 100MPa, 130MPa, 150MPa, 180MPa, 200MPa, 220MPa, 250MPa, or within the range formed by any of the above values. The present application shows that the negative electrode material has a high compressive resistance by measuring the compressive strength of the first amorphous carbon and the compressive strength of the negative electrode material within the above range. On the one hand, it can reduce the crushing ratio of the negative electrode material during the rolling process, and on the other hand, it can reduce the rupture of the negative electrode material during the charge and discharge cycle, thereby improving the battery cycle performance.
[0056] In the present application, the compressive strength of the material may be tested using methods and equipment known in the art. For example, the test may be performed with reference to GB / T 43091-2023 powder compressive strength test method.
[0057] In some optional embodiments, the specific surface area of the negative electrode material is 0.5 to 50 m 2 / g; As an example, the specific surface area of the negative electrode material is 0.5m 2 / g,5m 2 / g,10m 2 / g,15m 2 / g,20m 2 / g,25m 2 / g,30m 2 / g,35m 2 / g,40m 2 / g,45m 2 / g,50m 2 / g, or within the range formed by any of the above values. When the specific surface area of the negative electrode material is within the above range, the liquid retention can be maintained, the conductivity is improved while the specific surface area is low, and the side reaction between the negative electrode material and the electrolyte can be suppressed.
[0058] In some optional embodiments, the average particle size of the negative electrode material is 1 μm to 20 μm; as an example, the average particle size of the negative electrode material is 1 μm, 5 μm, 8 μm, 10 μm, 13 μm, 15 μm, 18 μm, 20 μm, or within the range of any of the above values. When the average particle size of the negative electrode material is within the above range, the fast charging performance and energy density of the battery can be guaranteed, and the dispersion performance is good.
[0059] In some optional embodiments, based on the total pore volume of the negative electrode material, the micropore volume of the negative electrode material accounts for 40% to 85%. As an example, the micropore volume of the negative electrode material accounts for 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, or within the range of any of the above values. When the micropore volume of the negative electrode material accounts for the above range, the electrolyte can have higher wettability and accelerate the migration rate of lithium ions.
[0060] In some optional embodiments, the degree of graphitization Id / Ig of the negative electrode material is 0.2 to 2.5. As an example, the degree of graphitization Id / Ig of the negative electrode material is 0.2, 0.5, 0.8, 1.0, 1.2, 1.5, 1.7, 2.0, 2.3, 2.5, or within the range of any of the above values. In the present application, the larger the Id / Ig ratio, the higher the proportion of defects or amorphous carbon structures relative to ordered graphite or graphene structures in the sample. In other words, the lower the degree of graphitization of the material, the richer the defects. Conversely, if the Id / Ig ratio is small, it means that the material is relatively pure, has fewer defects and a higher degree of graphitization. The higher the degree of graphitization, the higher the conductivity.
[0061] In the present application, the graphitization degree Id / Ig is tested using Raman spectroscopy, wherein the Id peak (D peak) usually appears at about 1300 cm -1 Nearby, the Ig peak (G peak) is located at about 1580cm -1 Nearby, the degree of graphitization Id / Ig is the peak area ratio.
[0062] In some optional embodiments, the proportion of silicon-based materials is 5% to 30% based on the total mass of the negative electrode material. As an example, the proportion of silicon-based materials is 5%, 8%, 10%, 13%, 15%, 17%, 20%, 22%, 25%, 28%, 30%, or within the range of any of the above values. By limiting the proportion of silicon-based materials, the present application takes into account the high energy density and low volume expansion rate of the negative electrode material.
[0063] According to a typical embodiment of the present application, a method for preparing a negative electrode material is provided, comprising: sulfonating, carbonizing and activating a carbon source precursor to generate a first amorphous carbon, introducing a silicon source into the first amorphous carbon to form a filled silicon-based material, and then introducing a carbon source to form a filled carbon material and a coating layer.
[0064] In some optional embodiments, the carbon source precursor includes but is not limited to one or more of asphalt-based materials, resin-based materials, coal-based materials, and biomass-based materials; spray granulation is performed, and Dn50 is controlled at 1 to 100 μm, preferably 1 to 20 μm, and its shape includes: spherical, square, diamond, layered, annular, etc., preferably spherical.
[0065] The sulfonation treatment step includes: placing the carbon source precursor prepared by spray granulation in a rotary kiln, adding a sulfonating agent, and performing a temperature-raising sulfonation treatment.
[0066] The sulfonating agent includes at least one of concentrated sulfuric acid, oleum, sulfur trioxide, chlorosulfonic acid, aminosulfonic acid, sulfuryl chloride, and sulfite, preferably concentrated sulfuric acid, oleum, and sulfur trioxide; the sulfonating agent causes the surface of the sulfonated carbon source precursor to have sulfonic acid groups, and the sulfone groups generated after sulfonation enhance the internal cross-linking strength of the carbon source precursor, and the final product, the first amorphous carbon, has the characteristics of high strength and strong high-temperature stability.
[0067] The sulfonation temperature is between 75° C. and 370° C., the sulfonation time is between 1 h and 8 h, and the sulfonation process may include pretreatment. For example, when a liquid sulfonating agent is used, the carbon source precursor may be soaked in the liquid sulfonating agent in advance to improve the final sulfonation effect.
[0068] The carbonization temperature is between 400 and 1500° C., and the carbonization time is between 0.5 and 50 hours. The carbonization time and temperature affect the physical properties of the first amorphous carbon, such as the specific surface area and pore size, and also affect the subsequent structural strength of the first amorphous carbon.
[0069] The carbonized first amorphous carbon is placed in a rotary kiln, and a protective gas (nitrogen, argon) is introduced to place it in a protective atmosphere, and oxygen, carbon dioxide, water vapor, etc. are introduced for activation, and the porosity, specific surface area, pore size and other parameters of the first amorphous carbon are further adjusted. The temperature is controlled at 800-1000°C and the time is 0.5-8h.
[0070] The activated first amorphous carbon is placed in a rotary kiln, and silane (or dichlorosilane, trichlorosilane, silicon tetrachloride) with a volume concentration of 2% to 5% is introduced, the diluent gas is hydrogen, the pressure in the furnace is controlled to be 0 to 0.1 MPa, the reaction time is 0.5 to 6 hours, and silane is allowed to enter the first amorphous carbon pores, the temperature is controlled to be 500 to 900°C, and then the temperature is controlled between 700 and 1200°C, and acetylene gas with a volume concentration of 20 to 30% is introduced, the diluent gas is argon, and the reaction time is 1 to 6 hours, so that acetylene enters the pore opening to form conductive carbon to block the pores, and a layer of carbon material is coated on the surface of the first amorphous carbon to complete the preparation of the negative electrode material, and the coating thickness of the outer surface and the amount of conductive material for blocking the pores in the pores are controlled by adjusting the time and temperature.
[0071] According to another aspect of the present application, a secondary battery is provided, the secondary battery comprising a negative electrode plate, the negative electrode plate comprising the negative electrode material described above;
[0072] The peeling force of the negative electrode sheet is 20N / m to 30N / m. As an example, the peeling force of the negative electrode sheet is 20N / m, 22N / m, 25N / m, 27N / m, 29N / m, 30N / m, or within the range formed by any of the above values. In the present application, the negative electrode sheet adopts the above-mentioned negative electrode material as the main material. The structure and particle characteristics of the above-mentioned negative electrode material are conducive to the dispersion of the negative electrode material and its contact with the adhesive, thereby improving the peeling force of the negative electrode sheet. The peeling force of the electrode sheet is within the above range, which can reduce the powder loss phenomenon during the battery cycle, and can also improve the internal resistance of the battery, which has a positive effect on the battery cycle performance and rate performance.
[0073] In this application, the peel force testing method includes the following steps:
[0074] 1. Cutting the negative electrode
[0075] Take the negative electrode sheet after rolling and use a customized sampler to cut the negative electrode sheet, which is generally 200mm long and 40mm wide.
[0076] 2. Paste and fix the negative electrode
[0077] Prepare a flat thin steel plate with a length of about 300mm and a width of about 60mm. Paste a double-sided tape in the center of the steel plate, making sure that the length of the double-sided tape is greater than the test length of the sample and is the same width as the negative electrode. Use a 4kg roller to smooth the double-sided tape back and forth 5 times to make it fit tightly in the center of the steel plate. Remove the covering paper of the double-sided tape, stick the negative electrode on the tape, and use a 4kg roller to smooth the double-sided tape back and forth 5 times to ensure that the negative electrode is completely matched with the tape to ensure that the width remains consistent when testing the peel force.
[0078] 3. Installation test
[0079] Insert the steel plate with the negative electrode sheet pasted and fixed into the lower fixture of the tensile testing machine and fix it vertically. Clamp the unpasted negative electrode sheet on the upper fixture of the tensile testing machine and fix it at 180° with the negative electrode sheet of the lower clamp. Calibrate and reset, set the test width, peeling length and speed. Start the test with a maximum displacement of 150mm, and obtain the peeling strength curve and average value. When processing the data, select the data with a test displacement of 20mm to 100mm to obtain the standard curve, and the result is the average peeling force.
[0080] According to another aspect of the present application, there is provided an electrical device comprising the above-mentioned secondary battery.
[0081] The secondary battery described in this application can be used as a power source for the electrical equipment, and can also be used as an energy storage unit for the electrical equipment. The electrical equipment can be, but is not limited to, mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc. The electrical equipment can select secondary batteries, battery modules or battery packs according to its usage requirements.
[0082] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0083] Example 1
[0084] This embodiment provides a negative electrode material, and the preparation method thereof includes the following steps:
[0085] S1, spray granulation: spray granulation of the carbon source precursor styrene-divinylbenzene copolymer to obtain precursor particles, and the particle Dn50 is controlled at 12 μm;
[0086] S2, sulfonation treatment: the precursor particles are placed in a rotary kiln, and commercially available 98% concentrated sulfuric acid (sulfonating agent) is added, and the temperature is raised to 350° C., and the sulfonation treatment is performed for 3 hours to obtain sulfonated precursor particles;
[0087] S3, carbonization treatment: calcining the sulfonated precursor particles at a temperature of 800° C. for 4 hours to obtain carbonized particles;
[0088] S4, activation treatment: putting the carbonized particles into a rotary kiln, introducing a protective gas (argon) to place them in a protective atmosphere, and introducing water vapor for activation, the temperature is controlled at 900° C., the time is 8 hours, and porous first amorphous carbon particles are obtained;
[0089] S5, active material deposition: the first amorphous carbon particles are placed in a rotary furnace, and silane with a volume concentration of 4% is introduced. The dilution gas is hydrogen. The pressure in the furnace is controlled to be 0.05MPa. The reaction time is 3 hours. Silane is allowed to enter the pores of the first amorphous carbon. The temperature is controlled at 600°C. Then the temperature is controlled at 900°C. acetylene gas with a volume concentration of 20% is introduced. The dilution gas is argon. The reaction time is 5 hours. Acetylene is allowed to enter the pore openings to form conductive carbon (second amorphous carbon), and the pores are sealed. A layer of carbon material is coated on the surface of the first amorphous carbon to complete the preparation of the negative electrode material.
[0090] Embodiments 2 to 4
[0091] This embodiment provides a negative electrode material. Compared with Embodiment 1, the difference is that the filling degree and the proportion of silicon-based materials are regulated by adjusting the temperature, time and silane concentration of silane introduction in step S5, as shown in Table 1 and Table 2 for details.
[0092] Embodiments 5 to 7
[0093] This embodiment provides a negative electrode material. Compared with Embodiment 1, the difference is that the specific surface area, total pore volume and mesoporous volume ratio of the first amorphous carbon are regulated by adjusting the activation time and temperature in step S4, as shown in Tables 1 and 2 for details.
[0094] Embodiments 8 to 10
[0095] This embodiment provides a negative electrode material. Compared with Embodiment 1, the difference is that the particle size of the primary particles and the particle size of the secondary particles of the second amorphous carbon are regulated by adjusting the temperature and time of the acetylene gas introduced in step S5, as shown in Table 1 and Table 2 for details.
[0096] Examples 11 to 13
[0097] This embodiment provides a negative electrode material. Compared with Embodiment 1, the difference is that the thickness of the coating layer is regulated by adjusting the acetylene gas introduction time and the carbon source gas content in step S5, as shown in Table 1 and Table 2 for details.
[0098] Embodiments 14 to 16
[0099] This embodiment provides a negative electrode material. Compared with Embodiment 1, the difference is that the specific surface area, average particle size and micropore ratio of the negative electrode material are regulated by adjusting the activation time, temperature and type of activator in step S4, as shown in Table 1 and Table 2 for details.
[0100] Embodiments 17 to 19
[0101] This embodiment provides a negative electrode material. Compared with Embodiment 1, the difference is that the compressive strength of the first amorphous carbon and the compressive strength of the negative electrode material are regulated by adjusting the sulfonation time and temperature of step S2, as shown in Table 1 and Table 2 for details.
[0102] Embodiments 20 to 22
[0103] This embodiment provides a negative electrode material. Compared with Embodiment 1, the difference is that the graphitization degree Id / Ig of the negative electrode material is regulated by adjusting the temperature of the carbonization treatment in step S3, as shown in Table 1 and Table 2 for details.
[0104] Comparative Examples 1-2
[0105] This comparative example provides a negative electrode material. Compared with Example 1, the difference is that the filling degree in the first amorphous carbon is controlled by adjusting the introduction temperature, time and silane concentration of the two gases in step S5, which is not within the range specified in this application. See Table 1 and Table 2 for details.
[0106] Table 1
[0107]
[0108] Table 2
[0109]
[0110] Test Case
[0111] The negative electrode materials provided in each embodiment and comparative example were used to prepare negative electrode sheets, and assembled into soft-pack batteries for performance testing. The specific preparation process of the soft-pack batteries and the battery testing method are as follows:
[0112] (1) Negative electrode preparation:
[0113] (a) Homogenization: Weigh the negative electrode materials prepared in each example or comparative example: carbon black: graphite: polyacrylic acid (PAA): styrene-butadiene rubber (SBR): carbon nanotube (CNT) = 10:1:86:2.4:0.5:0.1, and homogenize in a planetary mixer for 2 h, and add appropriate amount of deionized water to adjust the viscosity to 7000-8000 mPa·S;
[0114] (b) Coating: The negative electrode slurry is coated on a copper foil with a dedicated transfer coating device. The thickness of the copper foil is 8 μm. Interval coating is performed on both sides of the copper foil. The coated electrode is dried to obtain the negative electrode.
[0115] (c) Rolling: The above electrode sheets are rolled, dried and cut by a roller machine to obtain negative electrode sheets. The compaction density of the negative electrode sheets is 1.6 g / cm 3 .
[0116] (2) Cathode preparation
[0117] (a) Homogenization: Weigh the mass ratio of NCM523: conductive carbon black: PVDF: CNT: dispersant (polyvinyl pyrrolidone) = 97:0.8:1.4:0.7:0.1, put the ternary material, conductive carbon black, PVDF, and dispersant in a planetary mixer for dry mixing, and then add NMP and CNT for high-speed dispersion, and control the viscosity to 7000-8500 mPa·S;
[0118] (b) Coating: The positive electrode slurry is coated on the positive electrode current collector aluminum foil using a dedicated transfer coating device. The thickness of the aluminum foil is 10 μm, and intermittent coating is performed on both sides of the aluminum foil. The coated electrode is dried to obtain the positive electrode.
[0119] (c) Rolling: The above electrode sheets are rolled, dried, and cut to obtain positive electrode sheets. The compaction density of the positive electrode sheets is 3.45 g / cm 3 .
[0120] (3) Preparation of lithium-ion batteries
[0121] The prepared positive electrode sheet, negative electrode sheet and separator were wound up using a winding machine to obtain a winding core, which was packaged with an aluminum-plastic film and baked under vacuum for 48 hours to remove moisture. Then, an electrolyte was injected (the composition was a solvent with a mass ratio of EC:PC:DEC=2.5:3:5, a LiPF6 concentration of 1 mol / L, 5 wt% of fluoroethylene carbonate (FEC) and 0.5 wt% of vinylene carbonate (VC)), and the battery was then formed and divided into different capacities to produce a soft-pack battery (40 mm wide × 60 mm long × 8 mm thick).
[0122] (4) Battery performance test
[0123] 1. 25°C cycle test: At 25°C, the lithium ion batteries prepared in the embodiments and comparative examples were charged and discharged on a Xinwei tester at 1C / 1C and a voltage range of 2.5-4.25V until the capacity of the lithium ion battery was less than 80% of the initial capacity. The number of cycles of the lithium ion battery was recorded to characterize the cycle performance of the battery, in cycles.
[0124] 2. DCR test: At 25℃, discharge at 0.5C to 2.5V, then charge at 0.5C constant current to 4.25V, then charge at constant voltage to the cut-off current 0.05C, then discharge at 0.5C to 2.5V, record the discharge capacity at this time as C0, then fully charge with 0.5C0, then discharge for 60min to 50% SOC, finally discharge with 4C0 current for 10S, and read the DCR data.
[0125] 3. Wettability test:
[0126] S1: Cut the negative electrode sheet into a 50mm×50mm square;
[0127] S2: placing the cut negative electrode sheet under a contact angle tester, and using the contact angle tester to absorb 0.1 mL of electrolyte, which is the electrolyte used in the above lithium-ion battery preparation process;
[0128] S3: Observe with a microscope and record the time when the electrolyte beads are completely penetrated;
[0129] S4: Repeat the test on 3 negative electrode sheets and calculate the average penetration time in seconds.
[0130] 4. Battery energy density test
[0131] S1: At 25°C, discharge at 0.5C to 2.5V, then charge at 0.5C constant current to 4.25V, then charge at constant voltage to a cut-off current of 0.05C, and then discharge at 0.5C to 2.5V. Record the discharge capacity at this time as C1, in Ah;
[0132] S2: Calculate the average voltage V1 = discharge energy read by the equipment test software / discharge capacity C1, unit V;
[0133] S2: Weigh the weight of the soft-pack battery using an analytical balance, recorded as M1 in kg;
[0134] S3: Battery mass energy density = C1·V1 / M1, unit: Wh / kg.
[0135] The specific test results are shown in the table below:
[0136] Table 3
[0137]
[0138] It can be seen from the data in the above table that the present application deposits silicon-based materials and carbon materials inside the pores of the first amorphous carbon, and by limiting the filling degree within the above range, on the one hand, it can improve the compressive strength and compaction density of the negative electrode material and alleviate the expansion of the negative electrode material; on the other hand, it can leave appropriate pores to ensure the wettability of the electrolyte, increase the ion migration rate, achieve a positive effect on battery performance, and take into account both the energy density of the battery and the cycle performance of the battery.
[0139] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A negative electrode material, characterized in that: include: First, amorphous carbon has a plurality of pores; an active material, the active material comprising a silicon-based material and a carbon material, at least a portion of the silicon-based material and at least a portion of the carbon material being distributed in the pores; The filling degree of the silicon-based material and the carbon material in the first amorphous carbon is 30% to 80%, and the filling degree represents the ratio of effective pores of the first amorphous carbon filled by the silicon-based material and the carbon material.
2. The negative electrode material according to claim 1, characterized in that At least one of the following conditions is met: a. The specific surface area of the first amorphous carbon is 300 to 600 m 2 / g; b. The total pore volume of the first amorphous carbon is 0.8 to 3 cm 3 / g; c. In the first amorphous carbon, the mesopore volume accounts for 55% to 70% of the total pore volume of the first amorphous carbon.
3. The negative electrode material according to claim 1, characterized in that The carbon material includes a second amorphous carbon and a first graphitized carbon, wherein the second amorphous carbon includes at least one of conductive carbon black and coke; And / or, the first amorphous carbon includes hard carbon.
4. The negative electrode material according to claim 3, characterized in that The second amorphous carbon includes secondary particles formed by aggregation of primary particles. The particle size of the primary particles of the second amorphous carbon is 20 nm to 100 nm, and the particle size of the secondary particles is 50 nm to 200 nm.
5. The negative electrode material according to any one of claims 1 to 4, characterized in that: The invention also includes a coating layer distributed on at least a portion of the surface of the first amorphous carbon, wherein the coating layer includes second graphitized carbon.
6. The negative electrode material according to claim 5, characterized in that The coating layer has a thickness of 0.5 μm to 5 μm.
7. The negative electrode material according to any one of claims 1 to 4, characterized in that The compressive strength of the first amorphous carbon is 80 MPa to 200 MPa, and the compressive strength of the negative electrode material is 100 MPa to 250 MPa.
8. The negative electrode material according to claim 7, characterized in that The negative electrode material satisfies at least one of the following conditions: 1) The specific surface area of the negative electrode material is 0.5 to 50 m 2 / g; 2) The average particle size of the negative electrode material is 1 μm to 20 μm; 3) Based on the total pore volume of the negative electrode material, the micropore volume of the negative electrode material accounts for 40% to 85%.
9. The negative electrode material according to claim 7, characterized in that The graphitization degree Id / Ig of the negative electrode material is 0.2 to 2.
5.
10. The negative electrode material according to claim 7, characterized in that Based on the total mass of the negative electrode material, the silicon-based material accounts for 5% to 30%.
11. A secondary battery, characterized in that: The secondary battery comprises a negative electrode plate, and the negative electrode plate comprises the negative electrode material according to any one of claims 1 to 10; The peeling force of the negative electrode sheet is 20N / m to 30N / m.
12. An electrical device, characterized in that: The secondary battery according to claim 11 is included, and the secondary battery is used as a power supply for the electrical device.